Pelatihan Augmented Reality (AR) Untuk Meningkatkan Keterampilan Guru - Akto Hariawan; Hellik Hermawan; Retno Waluyo (Politeknik Negeri Cilacap, 2020)
The development of information technology in the world is currently experiencing very rapid development, especially in the field of mobile phones making it easier for people to get information through smartphones. This development also plays a role in the development of learning media. One of the development of learning media that is currently still new is learning media using Augmented Reality (AR). but the teacher of SMKN 1 Karanganyar does not know Augmented Reality so they do not have the skills to make Augmented Reality as an alternative learning media. Therefore it is needed Augmented Reality (AR) technology training for learning media. Community service activities have a goal that teachers can understand Augmented Reality (AR) and have the skills to make learning media using augmented reality. Community service uses a monological and dialogical approach. This augmented reality training activity was participated by 21 productive teachers from SMK N 1 Karanganyar. After the training, 95% of productive teachers of SMK N 1 Karanganyar have improved their skills so they already know about Augmented Reality (AR) and how to make Augmented Reality (AR) as an alternative learning media.